A qualitative systematic review of the reasons for parental attendance at the emergency department with children presenting with minor illness - Butun, Ahmet; Hemingway, Pippa (Elsevier, 2017)
Introduction: Over 5 million children attend the Emergency Department (ED) annually in England with an ever-increasing paediatric emergency caseload echoed globally. Approximately 60% of children present with illness and the majority have non-urgent illness creating burgeoning pressures on children’s ED and this crisis resonates globally. To date no qualitative systematic review exists that focuses on the parental reasons for childhood attendance at the ED in this subgroup.